Penerapan Teknologi Penginderaan Jauh untuk Kajian Indeks Kerapatan Vegetasi (NDVI) Tahun 2020 di Kecamatan Sirimau - Limehuwey, Resti; Kololu, Micky; Kotarumalos, Sitti Hafsa; Multi, Warni (Tanah Goyang : Jurnal Geosains, 2025)
This study aims to examine the distribution of vegetation density in Sirimau District using the NDVI method calculated from Landsat 8 satellite imagery. Landsat 8 imagery is processed to obtain NDVI values ​​that describe the level of vegetation density and health in the study area. The results of the analysis show that most of the Sirimau District area is dominated by dense vegetation with NDVI values ​​between 0.63 and 0.80 covering around 57.8% of the total area. In addition, vegetation is quite dense with NDVI values ​​between 0.42 and 0.63 and vegetation is not dense with NDVI values ​​between 0.21 and 0.42 occupying around 20.4% and 14.7% of the area, respectively. While non-vegetation and clouds and air only occupy a small part of the area with percentages of 7.1% and 0.003% of the total area, respectively. This study proves that the use of remote sensing technology, especially Landsat 8 imagery, is effective in mapping and integrating vegetation conditions quickly and accurately. The results of this study are expected to support natural resource management and spatial planning in Sirimau District.